"Muslims are the New Jews" in the West: Reflections on Contemporary Parallelisms. Issue 1 (2nd January 2016) - Shavit, Uriya
Abstract: This article examines a spectrum of contemporary texts by Muslim essayists, scholars and activists based in the Arab world, in Europe and in the USA that comparatively analyzed Jewish experiences in the West as invaluable lessons for Muslim minorities. These included: anti-Semitism and the struggle against it; segregation from and integration into majority societies; and, political lobbying on behalf of the "greater nation". The article argues that the diversity of Jewish realities, past and present, and the general sense that Jewish minorities in the West ultimately found ways to preserve their religious identity while amassing social-political influence, have rendered comparisons between Muslims and Jews an essential aspect of different (and at times contesting) arguments about the future of Muslim minorities in the West.